2008
DOI: 10.1111/j.1365-2036.2008.03701.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography accurately predicts presence of significant portal hypertension in patients with chronic liver disease

Abstract: SUMMARY BackgroundHepatic venous pressure gradient (HVPG) is a prognostic marker in patients with cirrhosis. Transient elastography measures liver stiffness (LS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
267
7
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(295 citation statements)
references
References 30 publications
16
267
7
5
Order By: Relevance
“…In addition, several studies [78,79] have shown a correlation between liver stiffness values and portal hypertension diagnosed by means of hepatic venous pressure gradient (HVPG) measurement, the gold standard for the diagnosis and staging of portal hypertension and a reliable predictor of clinical decompensation [80]. A correlation between liver stiffness values and the presence of esophageal varices has also been reported [79,[81][82][83][84]. However, liver stiffness measurement (LSM) cannot yet confidently predict the presence of esophageal varices in clinical practice and thus avoid the need for upper GI endoscopic screening of cirrhotic patients [85].…”
Section: Monitoring Of Disease Progressionmentioning
confidence: 94%
“…In addition, several studies [78,79] have shown a correlation between liver stiffness values and portal hypertension diagnosed by means of hepatic venous pressure gradient (HVPG) measurement, the gold standard for the diagnosis and staging of portal hypertension and a reliable predictor of clinical decompensation [80]. A correlation between liver stiffness values and the presence of esophageal varices has also been reported [79,[81][82][83][84]. However, liver stiffness measurement (LSM) cannot yet confidently predict the presence of esophageal varices in clinical practice and thus avoid the need for upper GI endoscopic screening of cirrhotic patients [85].…”
Section: Monitoring Of Disease Progressionmentioning
confidence: 94%
“…Similarly, McNemar-Bowker test was used for 3 ϫ 3 contingency table for assessing differences in the proportion of misclassified patients with 2 cutoffs of different noninvasive tests. In addition, the performance of previously published cutoffs for the identification of CSPH and varices derived from prospective studies was tested; namely we tested 13.6 kPa 29 and 21.1 kPa 30,31 for the prediction of CSPH, and 17.6 kPa for the prediction of varices. 29 Statistical analysis was performed with SPSS 16.0 package (SPSS, Chicago, IL), CIA software (v 2.2.0, University of Southampton, Southampton, UK) and MedCalc software (version 12.2.1.0, Belgium).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Besides, LS provides additional information in the setting of ESLD. Thus, studies conducted in HCVmonoinfected [16][17][18][19] and HIV/HCV-coinfected subjects 20 have demonstrated that the presence of esophageal varices can be predicted by LS. Moreover, LS correlates with portal hypertension, the hallmark of the evolution of chronic liver disease, in patients with HCV-related cirrhosis, 21,22 including those infected by HIV.…”
mentioning
confidence: 99%